2020
DOI: 10.24251/hicss.2020.516
|View full text |Cite
|
Sign up to set email alerts
|

Having Two Conflicting Goals in Mind: The Tension Between IS Security and Privacy when Avoiding Threats

Abstract: Despite users of personal IT devices perceive high risks of losing their personal data if their devices get lost or damaged, many are reluctant to use userfriendly online services (i.e., online backups) to recover from such incidents. We suggest that the reason for this denial are information privacy concerns because users need to disclose their personal files to the safeguard provider. As safeguarding services promise to reduce the IS security threat of losing data, individuals are subsequently tensed between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…Olt and Wagner [79] recently investigated the tension between the gain of security and the possible loss of privacy in the context of an online backup service. They combined the theory of goaldirected behavior [14] and the threat avoidance theory [65].…”
Section: Determinants Of Willingness To Disclosementioning
confidence: 99%
See 1 more Smart Citation
“…Olt and Wagner [79] recently investigated the tension between the gain of security and the possible loss of privacy in the context of an online backup service. They combined the theory of goaldirected behavior [14] and the threat avoidance theory [65].…”
Section: Determinants Of Willingness To Disclosementioning
confidence: 99%
“…When it comes to coping with security threats, the perceived effectiveness of a mechanism plays an important role when users select mitigation strategies [79,98]. Previous surveys showed that users' perceived usefulness is one of the strongest determinants of user attitudes towards biometric technology in general [37].…”
Section: Determinants Of Willingness To Disclosementioning
confidence: 99%
“…From the cybersecurity perspective, the notion of a trade-off, e.g., regarding convenience [44] or data privacy [45], is not new. In this context, information asymmetry negatively influences the balance between business value and cybersecurity risk.…”
Section: Theoretical Backgroundmentioning
confidence: 99%